Temperature-induced iron (III) reduction results in decreased dissolved organic carbon export in subalpine wetland soils, Colorado, USA. (1st July 2020) - Pallud, Céline; Rhoades, Charles C.; Schneider, Linden; Dwivedi, Pranjal; Borch, Thomas
Abstract: Concentrations of dissolved organic carbon (DOC) in surface waters have rapidly increased across Europe and North America over the past few decades. The causes for such trends have yet to be fully understood, although several factors including elevated temperatures and decreased atmospheric deposition of acid, nitrogen and sulfur, are considered responsible for the release of carbon from soils into streams. In order to determine how seasonal temperature patterns and soil physical and chemical characteristics influence iron (Fe)(III) reduction and DOC release to pore-water in subalpine wetland soils, we measured potential Fe(II) and DOC export rates at low (6 °C) and high (18 °C) temperatures using flow-through reactors containing undisturbed wetland soils sampled in the Fraser Experimental Forest (Colorado, USA) in two wetland types and at two depths. Higher temperature, soil organic matter, nitrogen, and extractable Fe concentrations, but lower soil C:N ratios and extractable manganese concentrations promoted Fe(II) export from soil to water. Additionally, Fe(III) reduction was 1.5–5 times more responsive to temperature in shallow, organic matter-rich soils, compared to organic-poor deeper soils. Conversely, DOC export declined at higher temperature in all soils, consistent with a temperature-related increase in carbon respiration by Fe(III)-reducers. While higher temperature is expected to reduce carbon storage in wetland soils, our findings suggest that temperature-related increase in Fe(III) reduction will not generate additional release of DOC from soils to rivers.